Functional measurement of immunization decision making - Pingenot, Alleene M. (Kansas State University, 2006)
Four variables from the HBM of healthcare behavior were used to examine immunization decision making by the lay public. Although there was evidence to support the HBM in general, results of these studies suggest that up to 70% of the variance in immunization decision-making could be explained by disease base rates alone. When there is a main effect of immunization side effects, this effect was entirely within the most severe category of side effect. In initial four experiments, there was a consistent interaction between the variable of disease type and the variables of disease severity and immunization side effects. The fifth experiment showed an interaction between disease type and immunization efficacy. Functional measurement was used to examine the nature of the interaction between the variables of disease base rates and immunization efficacy. This interaction is neither clearly additive nor multiplicative. Disease base rate dominates the other variables, although each modifies immunization likelihood somewhat in interaction with disease base rates. Furthermore, results suggest that participants did not appear to react to the difference between different disease base rates when the probabilities are small. Participants also did not conceptualize immunization efficacy as a conditional probability. Suggestions for how to address these issues via decision support were made. The principle contribution of this study, however, is development of a methodology. The method developed here investigates the variables of the HBM in an ecologically valid factorial design. This approach takes the HBM beyond description of variables to provision of prediction and generalizable results.
Keywords: Immunization; Decision-Making; Functional Measurment; Health Sciences, Public Health (0573); Psychology, Cognitive (0633)